Cultural specificity versus institutional universalism: a critique of the National Integrity System (NIS) methodology - Heywood, Paul M.; Johnston, Elizabeth (Springer, 2017)
This article provides an assessment and critique of the National Integrity System approach and methodology, informed by the experience of conducting an NIS review in Cambodia. It explores four key issues that potentially undermine the relevance and value of NIS reports for developing democracies: the narrowly conceived institutional approach underpinning the NIS methodology; the insufficient appreciation of cultural distinctiveness; a failure properly to conceptualise and articulate the very notion of ‘integrity’; and an over emphasis on compliance-based approaches to combating corruption at the expense of the positive promotion of integrity. The article seeks to offer some pointers to how the NIS approach could be adapted to broaden its conceptualisation of institutions and integrity, and thereby provide reports that are more theoretically informed as well as being more constructive and actionable.